Transtegrasi Ilmu dalam Persfektif Sejarah Filsafat - Fatonah, Fatonah; Harianto, Neldi; Hasan, Uswan; Defrianti, Denny; Syarifuddin, Amir (Universitas Batanghari Jambi, 2024)
This research aims to determine the historical development of philosophy and science as well as the transintegration of internal science from a philosophical perspective using the literature study method. Philosophy is considered to be the mother of science and is considered to be the first and last science which logically requires that other sciences be mastered, so that to understand philosophy one must also master other sciences, therefore philosophy can be transintegrated with various other sciences. In fact, to achieve true truth is knowledge. How philosophy can establish the transintegration of knowledge from various perspectives, one of which is history. To obtain the truth of philosophy when viewed from history. Human society, culture and the natural environment have a close relationship and are interconnected. This is what has structured and filled the history of philosophy with the various characteristics it carries and is inherent in. Based on these four things, philosophers generally divide philosophy into 4 (four) major traditions, namely Indian, Chinese, Islamic and Western philosophy. These 4 (four) great philosophical traditions gave birth to modern philosophy which then gave birth to the transintegration of science. Truth in philosophy and science is the truth of reason. Meanwhile, truth in religion is revelation. Thus, if philosophy, science and religion are united, there will be a transintegration of sophisticated and modern knowledge.